At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer: f (-1) = 9
Step-by-step explanation:
You just have to substitute -1 for x
f (-1) = -3 (-1)^2 + 2 (-1) - 5
f (-1) = 3^2 + -2 - 5
f (-1) = 9 - 7
f (-1) = 2
I think I'm correct so I hope this helped!
[tex]f(-1)=-3.(-1)^{2} +2.(-1)-5\\=\\-3.1+(-2)-5\\-3+(-2)-5\\-5-5=-10[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.